Study of Changes for Total Sialic Acid and Lipid-Bound Sialic Acid Levels in Tuberculosis and Lung cancer - Rissan, Wesam (University of Thi-Qar Journal of Science, 2011)
Sialic acid (SA) have been used as one of laboratory markers in diagnosis a variety ofpathological conditions, and it have been found to be elevated in a number of differentcancers .Many studies have shown that mean values of total sialic acid (TSA) or lipid-boundsialic acid (LSA) were higher in patients with cancer than in normal subjects .The aim of thepresent study was to determine the serum of total sialic acid (TSA), lipid-bound sialic acid(LSA),total protein (TP) and TSA/TP levels in the(Tuberculosis TB and Lung cancer LC )compared with healthy controls , data analysis indicated a significant increase ( P=0.0001 ) inTSA and LSA levels in (TB,LC) groups in comparison with healthy controls, no differencewas observed in TSA concentrations between (TB,LC) groups, no difference LSA levels wereobserved when (TB) patients compared with healthy controls ,.The concentration of TP wasslightly elevated( P=0.042 ) in (TB,LC) groups comparison with healthy controls ,there was a significant increased ( P=0.0001 ) in TSA/TP levels in (TB,LC) groups in comparison withhealthy controls.